2015
DOI: 10.1186/s12885-015-1383-x
|View full text |Cite
|
Sign up to set email alerts
|

High-recovery visual identification and single-cell retrieval of circulating tumor cells for genomic analysis using a dual-technology platform integrated with automated immunofluorescence staining

Abstract: BackgroundCirculating tumor cells (CTCs) are malignant cells that have migrated from solid cancers into the blood, where they are typically present in rare numbers. There is great interest in using CTCs to monitor response to therapies, to identify clinically actionable biomarkers, and to provide a non-invasive window on the molecular state of a tumor. Here we characterize the performance of the AccuCyte® – CyteFinder® system, a comprehensive, reproducible and highly sensitive platform for collecting, identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
120
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(125 citation statements)
references
References 22 publications
4
120
0
1
Order By: Relevance
“…Inexpensive, easy-to-use (Weitz et al, 1998) OncoQuick Density, Size Porous membrane above separation media for additional separation by filtration (Balic et al, 2005;Clawson et al, 2012;Lagoudianakis et al, 2009;M€ uller et al, 2005;Obermayr et al, 2010;Rosenberg et al, 2002) (Campton et al, 2015) Biophysical e Microfiltration in Two and Three Dimensions Size-based cell separation using pores or three-dimensional geometries.…”
Section: Densitymentioning
confidence: 99%
“…Inexpensive, easy-to-use (Weitz et al, 1998) OncoQuick Density, Size Porous membrane above separation media for additional separation by filtration (Balic et al, 2005;Clawson et al, 2012;Lagoudianakis et al, 2009;M€ uller et al, 2005;Obermayr et al, 2010;Rosenberg et al, 2002) (Campton et al, 2015) Biophysical e Microfiltration in Two and Three Dimensions Size-based cell separation using pores or three-dimensional geometries.…”
Section: Densitymentioning
confidence: 99%
“…Unlike enrichment approaches, there was no additional sample processing required for FAST cytometry that could result in reduced sensitivity due to cell loss. In 2015, Campton et al described and evaluated the performance of a comprehensive and highly sensitivity platform, the AccuCyte–CyteFinder system, for collecting, identifying, and collecting CTCs [17]. Nucleated cells were separated from blood with a density-based cell separation apparatus, AccuCyte, and transferred to microscopic slides.…”
Section: Introductionmentioning
confidence: 99%
“…Patient sample CTC counts matched or exceeded CellSearch CTC counts. Campton et al also showed that a single-cell retrieval device, CytePicke, can harvest individual CTCs from slides after identification with CyteFinder for further genomic analysis [17]. …”
Section: Introductionmentioning
confidence: 99%
“…l-ascorbic acid and superoxide dismutase (SOD) significantly increased the percentage of nonagglutinated, motile spermatozoa compared with the control but only by a moderate amount in comparison to PEN. Since l-ascorbic acid is a known reducing agent and SOD can chelate copper (Nordberg & Arnér 2001, Ottaviano et al 2008, it is possible that these secondary functions, as a reductant or chelator, contributed to this response (Fig. 5B).…”
Section: Discussionmentioning
confidence: 99%